Hubungan antara kompetensi profesional guru dan disiplin belajar terhadap hasil belajar IPA materi panas dan perpindahannya kelas V sekolah dasar - Mahmudah, Nurul; Rintayati, Peduk; Adi, Fadhil Purnama (Jurnal Pendidikan Dasar, 2023)
The purpose of this research is to 1) determine whether there is a relationship between teacher professional competence and science learning outcomes; 2) the relationship between learning discipline and science learning outcomes; 3) the relationship between teacher professional competence and learning discipline together with science learning outcomes. The method used is a correlational method. The sample is 86 students in grade 5th of 3 elementary schools. Data collection techniques use tests in the form and questionnaires. The data analysis technique used in this research is simple correlation analysis and double correlation analysis. Based on the results of data analysis, it can be concluded that 1) there is a significant relationship between teacher professional competence and science learning outcomes, namely the correlation coefficient rcount (0.457) > rtable (0.217) with a significance of tcount (4.712) > ttable (1.988); there is a significant relationship between learning discipline and science learning outcomes with a correlation coefficient of rcount (0.642) > rtable (0.217) with a significance of tcount (7.67) > ttable (1.988); there is a significant relationship between teacher professional competence and learning discipline together with science learning outcomes, namely  (0.687) > rtable (0.217), the significance of Fcount (37.0037) > Ftable (3.1065)